Sob o "fio da navalha": análise das ciências praticadas pelos pesquisadores da Educação Física em periódicos científicos (2005-2016) - Carneiro, Felipe Ferreira Barros (2019)
The aim of this thesis was to understand the profile of science practiced in scientific periodism that appears as a range of options in Brazilian Physical Education, comparing the characteristics of scientific practices inherent to the Biodynamic Subareas